Sex differences in the relationship of sleep-disordered breathing and asthma control among children with severe asthma. (3rd June 2022) - Gunnlaugsson, Sigfus; Greco, Kimberly F.; Petty, Carter R.; Sierra, Gabriella C.; Stamatiadis, Natalie P.; Thayer, Christine; Hammond, Adam G.; Giancola, Lauren M.; Katwa, Umakanth; Simoneau, Tregony; Baxi, Sachin N.; Gaffin, Jonathan M.
Abstract: Objective: Children with severe asthma are underrepresented in studies of the relationship of sleep-disordered breathing (SDB) and asthma and little is known about sex differences of these relationships. We sought to determine the relationship of SDB with asthma control and lung function among boys and girls within a pediatric severe asthma cohort. Methods: Patients attending clinic visits at the Boston Children's Hospital Pediatric Severe Asthma Program completed the Pediatric Sleep Questionnaire (PSQ), Asthma Control Test (ACT) and Spirometry. The prevalence of SDB was defined as a PSQ score >0.33. We analyzed the association between PSQ score and both ACT score and spirometry values in mixed effect models, testing interactions for age and sex. Results: Among 37 subjects, mean age was 11.8 years (4.4) and 23 (62.2%) were male, the prevalence of SDB was 43.2% (16/37). Including all 80 observations, there was a moderate negative correlation between PSQ and ACT scores (r=-0.46, p < 0.001). Multivariable linear regression models revealed a significant sex interaction with PSQ on asthma control ( p = 0.003), such that for each 0.10 point increase in PSQ there was a 1.88 point decrease in ACT score for females but only 0.21 point decrease in ACT score for males. A positive PSQ screen was associated with a 9.44 point (CI 5.54, 13.34, p < 0.001) lower ACT score for females and a 3.22 point (CI 0.56, 5.88, p = 0.02) lower score for males. Conclusions: SDB is common among children with severe asthma. Among children with severe asthma, SDB in girls portends to significantly worse asthma control than boys. Supplemental data for this article is available online at https://doi.org/10.1080/02770903.2021.1897838 .